The new TNM-based staging of breast cancer. - Cserni Gábor (VIRCHOWS ARCHIV, 2018)
This review describes the changes that have been implemented in the Tumor-Node-Metastasis (TNM)-based staging of breast cancers by the new, 8th editions of the relevant Union for International Cancer Control (UICC) and American Joint Committee on Cancer (AJCC) publications. After giving a background for TNM being the common language of cancer staging and related activities like cancer treatment and registration, it summarizes not only the changes but reviews some highlights important for pathologists, and lists and comments on the differences between the publications and diagnostic practices based on them. A section is dedicated to the prognostic stages of breast carcinomas introduced in the AJCC Cancer Staging Manual, but not mentioned in the UICC TNM classification of malignant tumors. A few issues that are not appropriately covered by TNM according to the authors' view (e.g., multifocal tumors, larger lymph node metastases identified by molecular methods, the heterogeneous prognosis of M1-defined stage IV disease) close the review with the final thoughts raising the vision of a potential loss of the common staging language.